Evaluation of the feasibility, safety, and preliminary effectiveness of hyperthermic intraperitoneal chemotherapy following radical surgery for locally advanced gastric cancer - Zhang, Tianze; Yu, Hang; Wang, Lang; Zhao, Shijun; Zhao, Cheng; Chai, Jie; Wang, Dehai (Frontiers in Oncology, 2025)
ObjectiveTo explore the feasibility, safety, and potential association between hyperthermic intraperitoneal chemotherapy (HIPEC) and peritoneal recurrence in patients with locally advanced gastric cancer following D2 radical surgery.Materials and methodsA retrospective analysis was conducted on 156 patients with locally advanced gastric cancer treated with D2 surgery at two centers between 2014 and 2023. Clinical outcomes and adverse events were assessed.ResultsBaseline characteristics were comparable between the HIPEC group (n = 70) and the surgery-only group (n = 86). The 2-year peritoneal recurrence rate was lower in the HIPEC group (18.6% vs. 34.9%, P=0.0206). Several factors—including high Charlson Comorbidity Index, advanced T stage, vascular invasion, intraoperative blood loss, and absence of HIPEC—were associated with higher recurrence risk. No significant differences were observed in perioperative complications between the groups or among different HIPEC frequencies (all P > 0.05).ConclusionIn this real-world dual-center study, HIPEC following D2 surgery was found to be feasible and safe, and was associated with a reduced risk of peritoneal recurrence in patients with locally advanced gastric cancer. These observational findings warrant further validation in randomized controlled trials.